Planting Media Combination Effect on the Growth of Mucuna Bracteata Seeds by Applying Vermicompost - Anna Kusumawati; Hendy Riyanto (Journal of Global Sustainable Agriculture, 2021)
This research was conducted to determine the effect of the combination of planting media on the growth of Mucuna bracteata by applying vermicompost. The research had been carried out in the practical garden of the Polytechnic of Lembaga Pendidikan Perkebunan, Wedomartani, Yogyakarta for 2 months from September to October 2019. The research method used a non-factorial randomized block design (RBD) with five treatments. The treatment carried out was a combination of planting media, between soil and vermicompost, namely P0 (100% soil), P1 (80% soil and 20% vermicompost), P2 (60% soil and 40% vermicompost), P3 (40% soil and 60% vermicompost) and P4 (20% soil and 80% vermicompost). The parameters observed in the study were plant height, number of leaves, and stem diameter. The results showed that the growth of Mucuna bracteate seedlings was influenced by the application of vermicompost. The highest plant height and stem diameter in Mucuna bracteate seedlings were obtained in P3 treatment (40% soil and 60% vermicompost), while the highest number of leaves was obtained from P4 treatment (20% soil and 80% vermicompost). Vermicompost can increase soil support for the growth of Mucuna bracteate seedlings so the growth of Mucuna bracteate increases.